Pemanfaatan Bahan Alami Sebagai Rodentisida Dan Pengusir Tikus Pada Kelompok Tani Di Desa Negeri Agung, Kecamatan Gunung Pelindung, Kabupaten Lampung Timur - Emantis Rosa; Yulianti; Enur Azizah (CV. Multi Kreasi Media, 2024)
One of the pests that is a problem for plants is rats. As a result, it can cause a decrease in production, crop failure and can even cause plants to die and losses to farmers. To overcome rat pest attacks, it is necessary to control them. Farmers have not received much information on control efforts derived from natural ingredients. Hence, in this service activity, outreach was carried out on